Narrative from the historical Padang - Harun, Nor Zalina (IIUM Press, 2015)
This chapter discusses place familiarity as one of the salient dimension in people-place bonding or resident's emotional relationships with a place. it narrates people's feelings and perceptions towards old public spaces in Penang.